Penggunaan Ampas Kopi Sebagai Material Alternatif pada Produk Interior - Johanna Limantara; Purnama Esa Dora Tedjokoesoemo; Muhammad Taufan Rizqy (Intra, 2019)
Coffee consumption has become a trend and lifestyle, not only in Indonesia, but all around the world. Indonesia is known as the 4th largest coffee producer country after Brazil, Vietnam and Colombia. The higher the rate of coffee consumption in Indonesia, the higher the coffee waste will be produced. This research was conducted with the aim of reducing coffee waste to maintain environmental cleanliness in Indonesia.This research is an upcycling process of coffee pulp using quantitative approach techniques and experimental methods to find the percentage of material content so that it can be made into an alternative material in interior products. The material will use a combination of coffee and wood powder and resin gum. This material can be applied into 3 interiors, namely forming space, filling space, and decorating.